Environmental Degradation in Malaysia's Pahang River Basin and its Relation with River Pollution: Strategic Plan from Assessment to Mitigation using Geo-Informatics - Saher, Faisal Nadeem; Nasly, Mohamed Ali; Tuty Asmawaty, Abdul Kadir; Teruggi, Giacomo (2012)
This is an established truth that with the growing world, the environmental degradation process cannot avoid but the technology is a solution to minimize this process. A sustainable development depends on plans, which are design on the strong basis of comprehensive datasets. Under this research studies, the required datasets were generated using remote sensing and GIS system integrated with field GPS surveys. The representations of these datasets further analyzed to ensure the data quality and output results. The objectives of the study were to find out the Pahang River pollution and environmental threats by assessing and analyzing different data layers of topographical, geological, hydrological, land cover, GPS surveys and satellite image. The methodology adopted to achieve the desired goals and to combat the complexity of the hydro-environmental system of Pahang River drawn from the idea to integrate the engineering tools with the geo-informatics techniques. This resultant output of the project enabled to develop a system of system for the existing and future development datasets in different research institutions in Malaysia for the decision makers and researchers. This hydro-environmental system is GIS-based and primarily data driven. However, it also has features, which were included to develop a strategic plan for the assessment of environmental degradation and its mitigation measures by focusing on the concept of sustainable healthy river for future generations and environment friendly development activities in the watershed area of the Pahang River. The planed roadmap for response functions is the salient feature of this research study, which consists of quantitative and qualitative relationships that help to the decision makers to make it understand how changes in the state of environment and river water will take part in the mitigation process for the environment degradation process.